Faktor-Faktor yang Mempengaruhi Kejadian Baby Blues - A, Nurmala Sinta; Limoa, Erlyn; Abidin, Nuraini (Innovative: Journal Of Social Science Research, 2024)
The aim of this research is to identify factors that influence the occurrence of baby blues. The method used is a literature review with a story narrative review. Results: In this literature, there are 20 articles collected with a limit of 2020–2024, and each article has been thoroughly analyzed regarding the factors that influence the incidence of baby blues. 16 articles mentioned the age factor, 14 articles mentioned the education factor, 15 articles mentioned the parity factor, and 13 articles mentioned the opportunity factor. Conclusion: Based on the findings found and researched in this literature review, it can be concluded that the age factor is the most important. Parity, education, and family support are the next most important factors. However, there are several additional components, such as employment, income, and type of birth.